An unusual occurrence of isolated thoracoschisis - Derek de Grijs; Narek Israelyan; Greggory R. DeVore; Steve C. Chen; Shant Shekherdimian (Elsevier, 2017)
Thoracoschisis is a rare congenital malformation that is frequently associated with limb and abdominal wall defects. Here we present only the third case of isolated thoracoschisis with no associated limb abnormalities. A female infant was born at 38 weeks via C section and was found to have a chest wall defect measuring 2 × 2 cm superior to a low-set left nipple. Reduction of eviscerated abdominal contents including liver, stomach, and transverse colon with closure of overlying skin was successfully performed on first day of life. The unique findings in the current case could ultimately shed light on the pathophysiology of thoracoschisis and its embryological origins.